Aluminum stress stimulates the accumulation of organic acids in root apices of Brachiaria species - Wenzl, Peter; Chavez, Alba L.; Patiño, Gloria M.; Mayer, Jorge Edgard; Rao, Idupulapati M. (Wiley, 2002)
Aluminum‐resistant Brachiaria decumbens Stapf cv. Basilisk (signalgrass) and closely related, but less resistant Brachiaria ruziziensis Germain & Evrard cv. Common (ruzigrass) both accumulated high concentrations of aluminum (Al) in roots. Approximately two thirds of the total Al was complexed by soluble low‐molecular‐weight ligands, suggesting that it had been taken up into the symplasm. We therefore investigated whether these species might employ Al‐chelating organic acids for internal detoxification of Al taken up by root apices, the primary site of Al injury. Unlike root apices of other Al‐resistant plant genotypes, which secrete organic‐acid anions to detoxify Al externally, apices of Brachiaria species accumulated organic acids within the tissue. A comparison with whole roots showed that this preference for accumulation (as opposed to secretion) was restricted to apices. Citric acid, and to a lesser extent trans‐aconitic acid, accumulated in a uniform dose‐dependent manner in root apices of both species as their Al content increased under Al‐toxic growth conditions. Their accumulation was accompanied by a stimulation of malate synthesis in Al‐resistant B. decumbens, while it occurred at the expense of malate in Al‐sensitive B. ruziziensis. These data suggest a role of organic acids in the internal detoxification of Al in root apices of both Brachiaria species, presumably contributing to their comparatively high basal level of Al resistance. Yet internal detoxification of Al by organic acids does not appear to be the principal mechanism responsible for the superior resistance of B. decumbens.